Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/978-3-642-13577-4_17
|View full text |Cite
|
Sign up to set email alerts
|

A Roadside Unit Placement Scheme for Vehicular Telematics Networks

Abstract: Abstract. This paper designs and measures the performance of a roadside unit placement scheme for the vehicular telematics network, aiming at improving connectivity and reducing the disconnection interval for the given number of roadside units, the transmission range, and the overlap ratio on the road network of Jeju city. The placement scheme begins with an initial selection that every intersection is the candidate. For each circle surrounding the candidate position with the radius equal to the transmission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 8 publications
0
54
0
5
Order By: Relevance
“…Lee and Kim [7] proposed a roadside unit placement scheme for vehicular networks, aiming at improving connectivity and reducing the disconnection interval for the given number of roadside units, the transmission range, and the overlap ratio on the road network of Jeju island. Performance measurement results obtained using the real-life movement history data in Jeju city showed that about 72.5% of connectivity can be achieved when deploying 1,000 RSUs, being the transmission range 300 m, while the disconnection time is mostly kept below 10 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Kim [7] proposed a roadside unit placement scheme for vehicular networks, aiming at improving connectivity and reducing the disconnection interval for the given number of roadside units, the transmission range, and the overlap ratio on the road network of Jeju island. Performance measurement results obtained using the real-life movement history data in Jeju city showed that about 72.5% of connectivity can be achieved when deploying 1,000 RSUs, being the transmission range 300 m, while the disconnection time is mostly kept below 10 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…The authors identify that roadside infrastructure should be placed at intersections rather than the middle of road segment. While the above studies are based on simulation data, a realistic trace of traffic is used to evaluate different schemes for RSU placement in [12]. The authors use a greedy algorithm to determine the minimum number and locations of RSUs that can serve all vehicles in Jeju city, Korea.…”
Section: B Simulation Resultsmentioning
confidence: 99%
“…RSE (Roadside Equipment) 9,10 and OBU (On-Board Unit) 11,12 with electric generators employ the way to use the independent communication channel; one RSE supports multiple connections of OBUs and reuses frequency, with which a transmitter with the output power of 10mW can secure communication area 13 . As it secures high success rate of communication and high speed mobility, it has been used for a traffic information collection system such as the bus information system.…”
Section: Dsrc (Dedicated Short Range Communication)mentioning
confidence: 99%